Treatment of an Endo-Perio Lesion with Ozone Gas in a Patient with Aggressive Periodontitis: A Clinical Case Report and Literature Review - Makeeva MK; Daurova FY; Byakova SF; Turkina AY (Dove Medical Press, 2020)
Maria K Makeeva,1,2 Fatima Yu Daurova,1 Svetlana F Byakova,2 Anna Yu Turkina2 1Conservative Dentistry Department, People’s Friendship University of Russia (RUDN University), Moscow, Russia; 2Therapeutic Dentistry Department, I.M. Sechenov First Moscow State Medical University (Sechenov University), Moscow, RussiaCorrespondence: Maria K MakeevaConservative Dentistry Department, Peoples Friendship University of Russia (RUDN University), Mikluho-Maklaya Street 10-2, Room 267, Moscow 117198, RussiaTel +79057416437Email abrek93@mail.ruAbstract: The pulp and periodontium have obvious relationships that have been described in many studies. Pulp infections may affect periodontal tissues and vice versa. Teeth with endo-perio lesions have a worse prognosis than isolated endodontic or periodontal lesions. Elimination of endodontic and periodontal infections is essential for successful treatment, so co-operation between endodontists and periodontists is necessary. In this clinical case, a 44-year-old male presented with primary periodontal disease with secondary endodontic involvement in his lower right canine because of aggressive periodontitis. There was 10 mm of clinical attachment loss and 8 mm periodontal pocket mesial from the tooth and bone radiolucency periapical and lateral from the root. Periodontal therapy was followed by endodontic treatment. Periodontal therapy included root scaling and planing, treatment of the periodontal pocket with ozone gas, systemic antibiotics, oral hygiene instructions, and chlorhexidine rinsing. Endodontic therapy included root canal instrumentation with rotary endodontic files, irrigation, root canal treatment with ozone gas, and obturation with lateral compaction. Radiographs at a 6-month follow-up appointment showed complete healing of the periapical lesion and alveolar bone lateral to the root. Using an interdisciplinary approach to treat endo-perio lesions provides favorable clinical outcomes. Ozone therapy is beneficial for the successful treatment of endo-perio lesions with narrow periodontal pockets in patients with aggressive periodontitis and poor prognosis.Keywords: endo-perio lesion, ozone therapy, ozone gas